Bridging culture and nature: An ethnobotanical exploration of the Dayak Ga’ai in Berau Regency, East Kalimantan - Sari, Ulfah Karmila; Yusnikusumah, Tri Rizkiana; Akbar, Acep; Wiati, Catur Budi; Purba, Samuel Fery; Nisaa’, Ratri Ma’rifatun; Sari, Nilam; Adman, Burhanuddin; Wibisono, Yusub Wibisono (Ethnobotany Research and Applications, 2026)
Background: Dayak Ga'ai, who lived in Berau, East Kalimantan, has rich ethnobotanical knowledge reflecting their deep connection with nature. Ethnobotanical knowledge in Dayak Ga'ai communities does not exist in the form of comprehensive documentation; it is only passed down orally, so it is at high risk of being lost. Documenting and preserving this knowledge is crucial for cultural and environmental conservation. Methods: This study employs interview methodologies utilizing purposive sampling. We conducted interviews with 70 respondents from five villages. The questions encompass respondent characteristics and ethnobotanical aspects of local wisdom knowledge. We additionally investigated and cataloged the plant. The Use Value (UV), Relative Frequency of Citation (RFC), and Cultural Significance Index (ICS) are ethnobotanical indexes employed for data analysis. Results: The results show that 169 species belonging to 56 families are known and utilized in the live of Dayak Ga’ay community. Categorized into revealed that 13 species are used for cultural purposes, 15 species for handicrafts, 114 species for traditional medicine, 67 species for food, and 38 species for traditional tools and equipment. There are 7 species in each index, namely Calamus sp. (RFC = 0.61; UV = 2.46; ICS = 36), Goniothalamus macrophyllus (RFC = 0.56; UV = 2.78; ICS = 46), Eusideroxylon zwageri (RFC = 0.46; UV = 1.37; ICS = 15), Vitex pinnata (RFC = 0.41; UV = 0.83; ICS = 15), Shorea sp. (RFC = 0.37; UV = 1.48; ICS = 17), Licuala spinosa (RFC = 0.31; UV = 1.57; ICS = 40), and Curcuma longa (RFC = 0.30; UV = 0.60; ICS = 18). They found plants in forests, gardens, and yards. Conclusions: The Ga'ai Dayak utilize diverse plants. Nevertheless, the ethnobotanical knowledge of these plants is decreasing due to modernization, migration, and deforestation. It is necessary to conserve natural resources and incorporate ancient knowledge into contemporary conservation and educational initiatives. Keywords: Ethnobotany; Dayak Ga’ai; Traditional knowledge, Cultural heritage, Berau